If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + -2) = c Reorder the terms: 2(-2 + y) = c (-2 * 2 + y * 2) = c (-4 + 2y) = c Solving -4 + 2y = c Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2y = 4 + c Combine like terms: -4 + 4 = 0 0 + 2y = 4 + c 2y = 4 + c Divide each side by '2'. y = 2 + 0.5c Simplifying y = 2 + 0.5c
| -4b=-b-9 | | 7z-1/2=3z | | 150+2x=45-1x | | -3t=7-4t | | 9N+10Y=200 | | 150+2x=195-1k | | 3v+8=4v | | x^3y=-4 | | 6x+3x^2=500 | | (3y-5)(5y+6u-4)= | | 6n-11=9+n | | 100x-75=50x+75 | | 9(x-a)=y | | 3x+6x^2=500 | | 4x+6x^2=500 | | r=(b+a)m | | 121=i | | ((x-2)^(2)(x^(2)-1))/((x-1)^(2)(x^(2)-4)) | | -(5/8)a-20=-10 | | 3(x+8)=y | | 150x-(3100+5x+.1x^2)=0 | | x=1*0.75 | | (2x+1)(1+x)=2(1-x)+6 | | 7+-5=6+-2 | | 6(x+4)+4=-14 | | 3h=21/2 | | 4x^2+32x=-65 | | 8.4=-logx | | 495.4/713.36 | | 6.4=2p | | m-22/4-4m-27/5=1 | | x^2+16-16x+x^2=4-4x+x^2 |